2019
DOI: 10.1111/jssr.12595
|View full text |Cite
|
Sign up to set email alerts
|

Beyond “Heartless Conservative” and “Bleeding Heart Liberal” Caricatures: How Religiosity Shapes the Relationship Between Political Orientation and Empathy

Abstract: Is political orientation associated with self-reported empathy? Popular caricatures frame political orientation in terms of the "heartless conservative" and the "bleeding heart liberal." Yet, previous research has produced findings that present mixed evidence to support these caricatures. Using data from the 2004 General Social Survey, analyses show that the caricatures of the caring liberal and the cold-hearted conservative are supported by results for empathy-in which conservatives have lower levels of empat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…In addition to these primary considerations, we would like to briefly discuss some of our secondary contributions. In support of previous research, we confirmed that political conservatism is associated with lower levels of empathy [28][29][30][31][32][33][34][35], higher levels of authoritarian beliefs [48][49][50][51][52][53][54], and lower levels of several dimensions of perceived pandemic threat [1, 1 3 13-15, 17, 59-63]. Our analyses of our disaggregated conservatism index are also informative.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to these primary considerations, we would like to briefly discuss some of our secondary contributions. In support of previous research, we confirmed that political conservatism is associated with lower levels of empathy [28][29][30][31][32][33][34][35], higher levels of authoritarian beliefs [48][49][50][51][52][53][54], and lower levels of several dimensions of perceived pandemic threat [1, 1 3 13-15, 17, 59-63]. Our analyses of our disaggregated conservatism index are also informative.…”
Section: Discussionsupporting
confidence: 88%
“…The first link in our theoretical model suggests that political conservatism contributes to riskier pandemic lifestyles by reducing empathetic concern. While we are regularly inundated with popular depictions of "heartless conservatives" and "bleeding heart liberals, " research consistently shows that political conservatives tend to exhibit lower levels of compassion and empathy (i.e., less concern for the feelings and experiences of others) relative to their more liberal counterparts [28][29][30][31][32][33][34][35]. Cameron and Rapier [36,p.…”
Section: Empathymentioning
confidence: 99%
“…Our study suggests that this relationship may be attributable, in part, to differences in mattering. A central tenet of most religious traditions is to show kindness and perform charitable or supportive acts toward one's neighbor (Ellison 1992;Schieman, Bierman, and Upenieks 2019). Religious beliefs also gain efficacy through congregational networks that collectively and regularly reinforce such values and serve as conduits of social support.…”
Section: Discussionmentioning
confidence: 99%
“…One function of the social relationships formed within religious congregations are to facilitate enhanced feelings of significance toward others (Petersen and Roy 1985). What is more, given the emphasis placed on altruistic behavior toward one's neighbor in many religious faiths (Schieman, Bierman, and Upenieks 2019), frequent attenders might perceive an enhanced capability to enact positive changes in others' lives. These perceptions are likely rooted in beliefs that one's own action can or should make a difference to others.…”
Section: Dimensions Of Religiosity and Matteringmentioning
confidence: 99%
“…When the explanatory power of socio‐economic factors has diminished, scholars have looked for other potential accounts. A growing number of studies have found a connection between personality or personality traits , that is, relatively permanent individual characteristics, and political behavior (Arvan, 2013; Duspara & Greitemeyer, 2017; Eisenberg‐Berg & Mussen, 1980; Hasson et al., 2018; Jonason, 2014; Schieman et al., 2019; Unnever et al., 2005).…”
Section: Introductionmentioning
confidence: 99%